2003
DOI: 10.1016/j.stam.2003.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Geometry and energetics of Si60isomers

Abstract: The novel electronic, optical and super-conducting properties exhibited by C 60 and its assembled materials have greatly stimulated the scientists all over the world racing to study Si 60 . In this paper we performed an extensive search from eighteen isomers including cages, wires, and stuffed structures of Si. It is found that the fullerene cage is not stable, and the tricapped-trigonal-prism unit is not the structural unit for Si 60 . While the spherical compact structure is the most stable energetically, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Since the discovery of C 60 , exploration of similar silicon fullerenes has received considerable attention . This not only includes the analogs Si 60 but also other smaller cages .…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of C 60 , exploration of similar silicon fullerenes has received considerable attention . This not only includes the analogs Si 60 but also other smaller cages .…”
Section: Introductionmentioning
confidence: 99%
“…(2) it has been found recently that oxidation can enhance the synthesis of Si nanowires [4], and SiO 2 layer covers on the surface of Si nanowires [5]; (3) SiO 2 nanowire can be used not only as an intensive blue light emitter [6] but also as a nanosized electronic resonant tunnelling transistor; (4) silicon nanostructures attract great attention [7][8][9][10][11][12].…”
mentioning
confidence: 99%
“…13 Several other structural models have been proposed for Si 60 geometries in addition to the fullerene cage, including a tricapped-trigonal-prism (TTP), an endohedral fullerene model, and bulk-like fragment model. Using first-principles calculations at the DFT level, Sun et al 14,15 compared the energies of cages, wires, and stuffed geometries of Si 60 and found that the fullerene cage and the TTP structure are not energetically favorable, whereas the endohedral fullerene structures (SF1 and SF2) of Si 20 @Si 40 are the most stable. An endohedral fullerene structure of Si 10 @Si 50 is also more stable than a piece of diamond structure for Si 60 from genetic algorithm (GA) with NTB method.…”
Section: Introductionmentioning
confidence: 99%